Single-component heat-conducting organic silica gel composition and preparation method thereof
By using α,ω-trimethoxyoligodimethylsiloxane as a crosslinking agent and aluminate in a single-component silicone thermal bonding glue, the problems of shrinkage and hardness during the curing process are solved, and the advantages of high extrusion rate, low hardness and storage stability are achieved.
Patent Information
- Application Number
- CN202411505537.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-28
AI Technical Summary
Single-component silicone thermal bonding adhesives are prone to shrinkage and excessive hardness during the curing process, resulting in excessive stress on electronic components and affecting the thermal conductivity effect.
α,ω-trimethoxyoligodimethylsiloxane is used as a crosslinking agent to replace traditional low-molecular silanes, reduce crosslinking density and volatility of low-molecular silanes, and at the same time, the thermal filler is treated with aluminate to improve the anti-settlement performance and storage stability.
It effectively solves the problems of shrinkage and excessive hardness during curing, improves the extrusion rate and low hardness characteristics of the product, enhances storage stability, and avoids damage to electronic components.
Smart Images

Figure BDA0005103849270000021 
Figure BDA0005103849270000091 
Figure FDA0005103849250000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new organic silicon materials, and relates to an organic silicon composition, and in particular to a single-component heat-conductive organic silicon composition for electronics and electrical appliances, which has the advantages of high extrusion rate, low hardness and storage stability, and a preparation method thereof. Background Art
[0002] One-component dealcoholized silicone thermal conductive adhesive has excellent thermal conductivity, insulation, high-strength bonding, moisture resistance, anti-corona performance and shock absorption and buffering effects. It is resistant to high and low temperatures and has a temperature range of -45 to 200°C. It is widely used in bonding and sealing in consumer electronics, high-power communication power modules, new energy electronic modules and other fields.
[0003] With the centralization of electronic modules, the power of electronic components is getting higher and higher. Based on the need for heat dissipation, the thermal conductivity of adhesives is also getting higher and higher, that is, the content of thermal conductive fillers in the formula is getting higher and higher. The problem that follows is that on the one hand, thermal conductive fillers are prone to sedimentation, stratification, and even agglomeration after being stored for a period of time, affecting normal performance. On the other hand, the higher the content of thermal conductive fillers, the more obvious shrinkage will occur during the curing process of the product, and in severe cases, wrinkling will occur. In addition, the hardness after curing is too high, which puts too much stress on the components, resulting in the thermal conductivity effect failing to meet expectations, and even damaging the electronic components.
[0004] The Chinese patent publication number is CN114015411A, the publication date is February 8, 2022, and the name is "Condensation-type one-component thermally conductive silicone adhesive and preparation method invention", which discloses a condensation-type one-component thermally conductive silicone adhesive, and its raw material composition includes, by weight: 200 parts of alkoxy-terminated polydimethylsiloxane, 800-2400 parts of thermally conductive filler, 4-20 parts of surface modifier, 10-30 parts of cross-linking agent, 5-20 parts of catalyst, and 1-10 parts of adhesion promoter; the thermally conductive filler is nano calcium carbonate, aluminum oxide, zinc oxide, aluminum nitride and nitrogen The invention discloses a plurality of different combinations of boron sulfide; the surface modifier is a reflux product of hexadecyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-aminopropyl trimethoxysilane and vinyl trimethoxysilane reacted at a certain ratio at 100°C for 2 hours; the adhesion promoter is a reflux product of γ-aminopropyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, N-β-(aminoethyl)-aminopropyl methyl dimethoxysilane and γ-isocyanate propyl triethoxysilane reacted at a certain ratio at 120°C for 2 hours. The thermal conductive silicone adhesive of the invention has a low system viscosity, high extrudability, low shrinkage during curing, and no wrinkling; good storage stability, no obvious sedimentation and stratification phenomenon after storage for more than half a year; good adhesion to organic materials such as PC, PBT, PET, PVC, and ABS.
[0005] However, no separate solution has been proposed for the significant shrinkage that occurs during the curing process of the one-component silicone thermally conductive adhesive.
[0006] The most commonly used methods for reducing hardness in the relevant literature include:
[0007] 1. Add non-reactive polydimethylsiloxane plasticizer, but after adding it, it is easy to leak oil during long-term use, thus affecting the normal use of electronic components.
[0008] 2. The cross-linking density can be reduced by increasing the molecular weight of the base silicone oil. However, too high a molecular weight of the silicone oil will affect the final extrusion and construction performance of the one-component silicone thermal conductive adhesive. Summary of the invention
[0009] In order to solve the above problems, the present invention provides a one-component thermally conductive organic silicone composition and a preparation method thereof. The present invention uses α, ω-trimethoxy oligodimethylsiloxane with a suitable molecular weight to replace the commonly used low-molecular silanes such as methyltrimethoxysilane and vinyltrimethoxysilane as a cross-linking agent, thereby reducing the cross-linking density of the one-component organic silicone thermally conductive adhesive and the volatilization of the low-molecular silane during the curing process, effectively solving the problem of damage to electronic components caused by shrinkage during the curing process and excessive hardness after curing, and at the same time, aluminate is used to treat the thermally conductive filler to improve the product's anti-sedimentation performance and enhance storage stability.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] The present invention first provides a one-component thermally conductive organic silicone composition, which comprises, by weight: 100 parts of a base polymer, 600-1200 parts of a thermally conductive filler, 6-24 parts of a filler treatment agent, 4-20 parts of a cross-linking agent, 0.5-5 parts of a coupling agent, and 5-15 parts of a catalyst; wherein the cross-linking agent is α, ω-trimethoxy oligodimethylsiloxane.
[0012] As a preferred embodiment of the present invention, the base polymer is α,ω-dialkoxy polydimethylsiloxane, and the structural formula of the α,ω-dialkoxy polydimethylsiloxane is shown in Formula 1:
[0013]
[0014] Wherein, m is any integer between 80 and 500.
[0015] As a preferred embodiment of the present invention, the structural formula of the α,ω-trimethoxy oligodimethylsiloxane is shown in Formula 2:
[0016] Wherein, N is any integer between 5 and 80.
[0017] As a preferred solution of the present invention, the thermally conductive filler is aluminum oxide and / or aluminum hydroxide with different particle sizes.
[0018] As a preferred embodiment of the present invention, the filler treating agent includes at least one of bis(acetylacetonato)isopropylaluminate, diisopropoxyacetoacetic acid oleate aluminate, and diisopropoxyethylacetoacetate aluminate.
[0019] As a preferred embodiment of the present invention, the coupling agent includes one or a combination of two or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, octyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0020] As a preferred embodiment of the present invention, the catalyst includes at least one of neoalkoxy tris(methacryloyloxy) zirconate, neoalkoxy tris(neodecanoyloxy) zirconate, and neoalkoxy tris(dioctylphosphoyloxy) zirconate, and is matched with a primary chelated titanium catalyst, and the primary chelated titanium catalyst includes at least one of diisopropoxy bis(ethyl acetoacetate) titanate, diisopropoxy bis(acetylacetone) titanate, dibutoxy bis(ethyl acetoacetate) titanate, and diisobutoxy bis(ethyl acetoacetate) titanate.
[0021] In the present invention, the mass ratio of zirconate to titanate chelate is 1:1-1:5.
[0022] As a preferred embodiment of the present invention, the viscosity of the base polymer at 25° C. is 100-5000 mPa·s.
[0023] As a preferred embodiment of the present invention, the viscosity of the α,ω-trimethoxy oligodimethylsiloxane at 25° C. is 5-100 mPa·s.
[0024] The present invention also provides a method for preparing the above-mentioned one-component thermally conductive organic silicone composition, which comprises: adding a base polymer, a thermally conductive filler, and a filler treatment agent into a mixer with a heating and decompression system, heating to 110-130°C, stirring for 2-3 hours under a vacuum degree ≥ 0.09 MPa to obtain a thermally conductive composition base material, cooling the thermally conductive composition base material to room temperature, adding a crosslinking agent, a coupling agent, and a catalyst, and stirring for 30-60 minutes under a vacuum degree ≥ 0.09 MPa at room temperature to obtain a one-component thermally conductive organic silicone composition.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1) The present invention adopts α, ω-trimethoxy oligosiloxane as a crosslinking agent instead of low molecular weight silanes such as methyltrimethoxysilane, thereby reducing the crosslinking density of the product and the volatilization of the low molecular weight silane during the curing process, and effectively solves the problem of shrinkage during the curing process of the product and excessive hardness after curing causing excessive stress on electronic components and causing damage.
[0027] 2) The present invention uses aluminate to treat the thermally conductive filler, and fully treats the moisture content and surface hydroxyl groups of the filler, which can not only improve the processing performance of plastic products filled with inorganic powders, but also significantly improve the physical and mechanical properties of the products, reduce the water absorption rate of the products, reduce the oil absorption, and evenly disperse the thermally conductive filler, thereby improving the storage stability of the products.
[0028] 3) The present invention uses aluminate to treat the thermally conductive filler. The inorganic-philic end and the organic-philic end of the aluminate coupling agent can react chemically with the surface of the inorganic filler and the polyorganosiloxane, respectively, to form an entangled structure, thereby improving the anti-settling performance of the product.
[0029] 4) The present invention adopts zirconate and titanate chelate as catalysts, while taking into account the reaction activity and storage stability of the thermally conductive organic silicone composition product.
[0030] 5) The thermally conductive organic silicone composition of the present invention has the advantages of high extrusion rate, low hardness and storage stability, and can be applied to consumer electronics, new energy vehicles, communication electronics and other fields. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] The single-component dealcoholized thermally conductive silica gel composition of this embodiment comprises the following raw materials:
[0034] 100 parts of base silicone oil, α, ω-dimethoxy polydimethylsiloxane, structural formula:
[0035] m = 380, viscosity at 25°C is 1000 mPa·s;
[0036] 600 parts of thermal conductive filler, including 100 parts of 5 micron aluminum oxide and 500 parts of 25 micron aluminum oxide;
[0037] 12 parts of filler treatment agent, diisopropoxy acetoacetic acid oleate aluminate (purchased from Nanjing Nengde New Material Technology Co., Ltd.);
[0038] Crosslinking agent 10 parts, α, ω-trimethoxy oligodimethylsiloxane, structural formula:
[0039] n=50, viscosity at 25℃ is 50mPa·s; (purchased from Wuxi Quanli Chemical Co., Ltd., QLS-204);
[0040] 3 parts of coupling agent, including 1 part of γ-aminopropyltrimethoxysilane and 2 parts of γ-glycidoxypropyltrimethoxysilane (purchased from Jingzhou Jianghan Fine Chemical Co., Ltd.);
[0041] 10 parts of catalyst, including 5 parts of neoalkoxy tris (neodecanoyloxy) zirconate and 5 parts of diisopropoxy bis (ethyl acetoacetate) titanate (purchased from Nanjing Nengde New Material Technology Co., Ltd.).
[0042] The α,ω-dimethoxypolydimethylsiloxane, thermal conductive filler, and filler treating agent are added into a mixer with a heating and decompression system, the temperature is raised to 120° C., and the mixture is stirred for 3 hours under a vacuum degree of 0.09 MPa to prepare a thermal conductive composition base material;
[0043] After the base material of the heat-conductive composition is cooled to room temperature, a cross-linking agent, a coupling agent and a catalyst are added, and the mixture is stirred for 60 minutes at room temperature and a vacuum degree of 0.09 MPa to obtain a single-component heat-conductive organic silicone composition.
[0044] Example 2
[0045] The single-component dealcoholized thermally conductive silica gel composition provided in this embodiment comprises raw materials including:
[0046] 100 parts of base silicone oil, α, ω-dimethoxy polydimethylsiloxane, structural formula:
[0047] m = 380, viscosity at 25°C is 1000 mPa·s;
[0048] 800 parts of thermal conductive filler, including 200 parts of 5 micron aluminum oxide and 600 parts of 25 micron aluminum oxide;
[0049] 16 parts of filler treatment agent, bis(acetylacetonato)isopropylaluminate (purchased from Nanjing Nengde New Material Technology Co., Ltd.);
[0050] Crosslinking agent 10 parts, α, ω-trimethoxy oligodimethylsiloxane, structural formula:
[0051] n=50, viscosity at 25℃ is 50mPa·s; (purchased from Wuxi Quanli Chemical Co., Ltd., QLS-204);
[0052] 3 parts of coupling agent, including 1 part of γ-aminopropyltriethoxysilane and 2 parts of γ-glycidoxypropyltrimethoxysilane (purchased from Jingzhou Jianghan Fine Chemical Co., Ltd.);
[0053] 10 parts of catalyst, including 5 parts of neoalkoxy tris(methacryloyloxy) zirconate and 5 parts of diisopropoxy bis(ethyl acetoacetate) titanate (purchased from Nanjing Nengde New Material Technology Co., Ltd.).
[0054] The α,ω-dimethoxypolydimethylsiloxane, thermal conductive filler, and filler treating agent are added into a mixer with a heating and decompression system, the temperature is raised to 120° C., and the mixture is stirred for 3 hours under a vacuum degree of 0.09 MPa to prepare a thermal conductive composition base material;
[0055] After the base material of the heat-conductive composition is cooled to room temperature, a cross-linking agent, a coupling agent and a catalyst are added, and the mixture is stirred for 60 minutes at room temperature and a vacuum degree of 0.09 MPa to obtain a single-component heat-conductive organic silicone composition.
[0056] Example 3
[0057] The single-component dealcoholized thermally conductive silica gel composition provided in this embodiment comprises raw materials including:
[0058] 100 parts of base silicone oil, α, ω-dimethoxy polydimethylsiloxane, structural formula:
[0059] m = 380, viscosity at 25°C is 1000 mPa·s;
[0060] 900 parts of thermal conductive filler, including 300 parts of 5 micron aluminum oxide and 600 parts of 25 micron aluminum oxide;
[0061] 18 parts of filler treatment agent, diisopropoxyethyl acetoacetate aluminate (purchased from Nanjing Nengde New Material Technology Co., Ltd.);
[0062] Crosslinking agent 10 parts, α, ω-trimethoxy oligodimethylsiloxane, structural formula:
[0063] n=50, viscosity at 25℃ is 50mPa·s; (purchased from Wuxi Quanli Chemical Co., Ltd., QLS-204);
[0064] 3 parts of coupling agent, including 1 part of γ-aminopropyltriethoxysilane and 2 parts of γ-glycidoxypropyltrimethoxysilane (purchased from Jingzhou Jianghan Fine Chemical Co., Ltd.);
[0065] 10 parts of catalyst, including 5 parts of neoalkoxy tris (dioctyl phosphate acyloxy) zirconate and 5 parts of diisopropoxy bis (ethyl acetoacetate) titanate (purchased from Nanjing Nengde New Material Technology Co., Ltd.).
[0066] The α,ω-dimethoxypolydimethylsiloxane, thermal conductive filler, and filler treating agent are added into a mixer with a heating and decompression system, the temperature is raised to 120° C., and the mixture is stirred for 3 hours under a vacuum degree of 0.09 MPa to prepare a thermal conductive composition base material;
[0067] After the base material of the heat-conductive composition is cooled to room temperature, a cross-linking agent, a coupling agent and a catalyst are added, and the mixture is stirred for 60 minutes at room temperature and a vacuum degree of 0.09 MPa to obtain a single-component heat-conductive organic silicone composition.
[0068] Example 4
[0069] The single-component dealcoholized thermally conductive silica gel composition provided in this embodiment comprises raw materials including:
[0070] 100 parts of base silicone oil, α, ω-dimethoxy polydimethylsiloxane, structural formula:
[0071] m = 380, viscosity at 25°C is 1000 mPa·s;
[0072] 800 parts of thermal conductive filler, including 200 parts of 5 micron aluminum hydroxide and 600 parts of 25 micron aluminum oxide;
[0073] 16 parts of filler treatment agent, bis(acetylacetonato)isopropylaluminate (purchased from Nanjing Nengde New Material Technology Co., Ltd.);
[0074] Crosslinking agent 10 parts, α, ω-trimethoxy oligodimethylsiloxane, structural formula:
[0075] n=50, viscosity at 25℃ is 50mPa·s; (purchased from Wuxi Quanli Chemical Co., Ltd., QLS-204);
[0076] 3 parts of coupling agent, including 1 part of γ-aminopropyltriethoxysilane and 2 parts of γ-glycidoxypropyltrimethoxysilane (purchased from Jingzhou Jianghan Fine Chemical Co., Ltd.);
[0077] 10 parts of catalyst, including 5 parts of neoalkoxy tris(methacryloyloxy) zirconate and 5 parts of diisopropoxy bis(ethyl acetoacetate) titanate (purchased from Nanjing Nengde New Material Technology Co., Ltd.).
[0078] The α,ω-dimethoxypolydimethylsiloxane, thermal conductive filler, and filler treating agent are added into a mixer with a heating and decompression system, the temperature is raised to 120° C., and the mixture is stirred for 3 hours under a vacuum degree of 0.09 MPa to prepare a thermal conductive composition base material;
[0079] After the base material of the heat-conductive composition is cooled to room temperature, a cross-linking agent, a coupling agent and a catalyst are added, and the mixture is stirred for 60 minutes at room temperature and a vacuum degree of 0.09 MPa to obtain a single-component heat-conductive organic silicone composition.
[0080] Comparative Example 1
[0081] The thermally conductive silica gel composition provided in this comparative example comprises raw materials including:
[0082] 100 parts of base silicone oil, α, ω-dimethoxy polydimethylsiloxane, structural formula:
[0083] m = 380, viscosity at 25°C is 1000 mPa·s;
[0084] 800 parts of thermal conductive filler, including 200 parts of 5 micron aluminum oxide and 600 parts of 25 micron aluminum oxide;
[0085] Filler treatment agent 16 parts, vinyl trimethoxy silane;
[0086] Crosslinking agent 10 parts, α, ω-trimethoxy oligodimethylsiloxane, structural formula:
[0087] n=50, viscosity at 25℃ is 50mPa·s; (purchased from Wuxi Quanli Chemical Co., Ltd., QLS-204);
[0088] 3 parts of coupling agent, including 1 part of γ-aminopropyltriethoxysilane and 2 parts of γ-glycidoxypropyltrimethoxysilane (purchased from Jingzhou Jianghan Fine Chemical Co., Ltd.);
[0089] 10 parts of catalyst, including 5 parts of neoalkoxy tris(methacryloyloxy) zirconate and diisopropoxy bis(ethyl acetoacetate) titanate (purchased from Nanjing Nengde New Material Technology Co., Ltd.).
[0090] The preparation method is the same as that in Example 2.
[0091] Comparative Example 2
[0092] The thermally conductive silica gel composition provided in this comparative example comprises raw materials including:
[0093] 100 parts of base silicone oil, α, ω-dimethoxy polydimethylsiloxane, structural formula:
[0094] m = 380, viscosity at 25°C is 1000 mPa·s;
[0095] 800 parts of thermal conductive filler, including 200 parts of 5 micron aluminum oxide and 600 parts of 25 micron aluminum oxide;
[0096] Filler treatment agent 16 parts, bis(acetylacetonato)isopropylaluminate;
[0097] Crosslinking agent 10 parts, methyltrimethoxysilane;
[0098] 3 parts of coupling agent, including 1 part of γ-aminopropyltriethoxysilane and 2 parts of γ-glycidoxypropyltrimethoxysilane (purchased from Jingzhou Jianghan Fine Chemical Co., Ltd.);
[0099] 10 parts of catalyst, including 5 parts of neoalkoxy tris(methacryloyloxy) zirconate and diisopropoxy bis(ethyl acetoacetate) titanate (purchased from Nanjing Nengde New Material Technology Co., Ltd.).
[0100] The preparation method is the same as that in Example 2.
[0101] The one-component dealcoholized organic silicon thermally conductive adhesive prepared in Examples 1-4 and the thermally conductive silicone composition obtained in Comparative Examples 1-2 were tested, and the performance of the products is shown in Table 1.
[0102] Test method:
[0103] The present invention performs a performance test on the obtained single-component dealcoholized organic silicon thermal conductive adhesive, and the specific process is as follows:
[0104] 1) The thermal conductivity of the obtained one-component dealcoholized silicone thermal conductive adhesive was tested according to ISO / DIS22007 standard.
[0105] 2) The hardness of the obtained one-component dealcoholized silicone thermal conductive adhesive was tested according to the national standard GB / T 531.1-2008.
[0106] 3) The extrusion rate of the obtained one-component dealcoholized silicone thermal conductive adhesive was tested according to the national standard GB / T 13477.4, with the specific conditions being a pressure of 0.2 MPa and an extruder head diameter of 4 mm.
[0107] 4) The flame retardant properties of the obtained one-component dealcoholized silicone thermal conductive adhesive were tested according to UL94 standard.
[0108] Table 1. Test results
[0109]
[0110] It can be seen from Table 1 that by comparing the performance data of Example 2 and Comparative Example 1, it can be seen that compared with the commonly used organosilicon coupling agent treating agent vinyltrimethoxysilane, the aluminate-treated thermal conductive filler used in the present invention has a good anti-sedimentation effect and better storage stability after the final product is stored for six months.
[0111] It can be seen from the performance data of Example 2 and Comparative Example 2 that the present invention uses α, ω-trimethoxy oligodimethylsiloxane instead of methyltrimethoxysilane as a crosslinking agent, the hardness of the product is significantly reduced, and no shrinkage occurs during the curing process;
[0112] Example 4 is based on Example 2, but part of the aluminum oxide is replaced with aluminum hydroxide, and the thermal conductivity reaches 2.0 W / mk, and the UL94 flame retardant V0 grade can be achieved.
[0113] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A one-component thermally conductive organic silicone composition, characterized in that: The one-component thermally conductive organic silicone composition comprises, by weight: 100 parts of a base polymer, 600-1200 parts of a thermally conductive filler, 6-24 parts of a filler treatment agent, 4-20 parts of a crosslinking agent, 0.5-5 parts of a coupling agent, and 5-15 parts of a catalyst; wherein the crosslinking agent is α, ω-trimethoxy oligodimethylsiloxane.
2. A one-component thermally conductive organic silicone composition according to claim 1, characterized in that: The base polymer is α,ω-dialkoxy polydimethylsiloxane, and the structural formula of the α,ω-dialkoxy polydimethylsiloxane is shown in Formula 1: Wherein, m is any integer between 80 and 500.
3. The one-component thermally conductive organic silicone composition according to claim 1, characterized in that: The structural formula of the α,ω-trimethoxy oligodimethylsiloxane is shown in Formula 2: Wherein, N is any integer between 5 and 80.
4. The one-component thermally conductive organic silicone composition according to claim 1, characterized in that: The thermal conductive filler is aluminum oxide and / or aluminum hydroxide with different particle sizes.
5. The one-component thermally conductive organic silicone composition according to claim 1, characterized in that: The filler treating agent includes at least one of bis(acetylacetonato)isopropylaluminate, diisopropoxyacetoacetic acid oleate aluminate, and diisopropoxyethylacetoacetate aluminate.
6. The one-component thermally conductive organic silicone composition according to claim 1, characterized in that: The coupling agent includes one or a combination of two or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, octyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
7. The one-component thermally conductive organic silicone composition according to claim 1, characterized in that: The catalyst includes at least one of neoalkoxy tris(methacryloyloxy) zirconate, neoalkoxy tris(neodecanoyloxy) zirconate, and neoalkoxy tris(dioctylphosphoyloxy) zirconate, and is matched with a primary chelated titanium catalyst, wherein the primary chelated titanium catalyst includes at least one of diisopropoxy bis(ethyl acetoacetate) titanate, diisopropoxy bis(acetylacetone) titanate, dibutoxy bis(ethyl acetoacetate) titanate, and diisobutoxy bis(ethyl acetoacetate) titanate.
8. The one-component thermally conductive organic silicone composition according to claim 1, characterized in that: The base polymer has a viscosity of 100-5000 mPa·s at 25°C.
9. A one-component thermally conductive organic silicone composition according to any one of claims 1 to 8, characterized in that: The viscosity of the α,ω-trimethoxy oligodimethylsiloxane at 25° C. is 5-100 mPa·s.
10. A method for preparing the one-component thermally conductive organic silicone composition according to any one of claims 1 to 9, characterized in that: The preparation method comprises: adding a base polymer, a thermally conductive filler and a filler treatment agent into a mixer with a heating and decompression system, heating to 110-130° C., stirring for 2-3 hours under a vacuum degree of ≥0.09 MPa to prepare a thermally conductive composition base material, cooling the thermally conductive composition base material to room temperature, adding a crosslinking agent, a coupling agent and a catalyst, and stirring for 30-60 minutes under a vacuum degree of ≥0.09 MPa at room temperature to prepare a single-component thermally conductive organic silicone composition.
Citation Information
Patent Citations
Condensed type single-component heat-conducting silicone adhesive and preparation method thereof
CN114015411A